The Role of Youth Policy in The Processes of Modernization in China - Abdulkhaev Abdurashid Nodir ugli (Next Scientists International Journal JSSHRF, 2026)
The article discusses the features of the youth policy of the People's Republic of China, as well as the work of the party in this direction. The problems in the implementation of China's youth policy are revealed. The main directions of youth policy and measures taken by the country's leadership to address this issue are also analyzed. The article analyzes the economic factors that have had and are having an impact on the evolution of the youth policy of the People's Republic of China. An assessment of the results of the CPC leadership's policy regarding the implementation of youth policy is presented. The role of youth organizations in modern Chinese society and its impact on public life is considered.